The Influence of Psikoedukasi on Stress Management in Improving Self Efficacy and Coping Mechanism of Families in Caring for Caring for ODGJ Patient (Schizophrenia) at Public Health Center of Balowerti Kediri Regency - Eka Lutfiatus Solehah; Byba Melda Suhita; Yuly Peristiowati (Universitas STRADA Indonesia, 2019)
Families need to have the attitude of accepting patients, give a positive response, appreciate the patient as family members and foster an attitude of responsibility to the patient, so the balance of life in the family may occur. The existence of the soul in the family of disorders affecting the function of the family. Families that work well will be able to provide care on a family member with good and vice versa. Research objectives to analyzed the influence of psikoedukasi on stress management in improving self efficacy and mechanism of ODGJ in caring for families koping (Schizophrenia). Design research is to take the pretest-posttest alphabets experiment pre design. The research of the variable Psikoedukasi as the independent variable and self efficacy and mechanism of the dependent variables as koping.